Migration and new international actors : an old phenomenon seen with new eyes / edited by Maria Eugenia Cruset - Cruset, Maria Eugenia (ed.) (Tyne, 2012)
Recent studies on migration have been given a new focus and theoretical framework. The so-called (3z(Bpolitical dimension(3y (Bof Diasporas, and their action at the international level as agents of para-diplomacy, as well as the introduction of analysis of the trans-national character of the migratory phenomenon, allow us to dig deeply into the field of our investigations, taking us out of the narrow frame of the Nation State.s
Keywords: Migration